2013
DOI: 10.1080/10911359.2013.740336
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Social Work Students Engage in Lesbian and Gay Rights Activism?

Abstract: This paper considers the contexts and motivations as to why some social work students engage in lesbian and gay rights activism. To explain electoral and protesting modes of activism, this study utilized variables from resource, mobilizing, and framing theories of political participation to explain activism related to gay and lesbian rights. After gathering data on 159 undergraduate social work majors, regressions suggest that economic resources failed to explain participation in gay and lesbian politics. Inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…Several other factors identified by researchers include concepts reproducing the social -moral bonds (Buttaro and Battle, 2012) micropanics (Guittar, 2013) secure attachment style (Jellison and McConnell, 2003) racial discrimination against the ingroup (Craig and Richeson, 2014) the direct environment (Blaauw, 2012) maternal attitudes (Oksal, 2008) the intimacy of contact (Heinze and Horn, 2009;Smith et al, 2009) levels of aversion toward homosexuals (Ncanana and Ige, 2014); educational attainment, communicating with full-fledged activists, having an ability to recognize heterosexism and maintaining a commitment to social justice (Swank and Fahs, 2013) age, educational level, religious affiliation, contact with homosexual persons (Adela, 2010) higher levels of knowledge (Alderson et al, 2009) public policy (Hooghe and Meeusen, 2013) and government institution (Henshaw, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several other factors identified by researchers include concepts reproducing the social -moral bonds (Buttaro and Battle, 2012) micropanics (Guittar, 2013) secure attachment style (Jellison and McConnell, 2003) racial discrimination against the ingroup (Craig and Richeson, 2014) the direct environment (Blaauw, 2012) maternal attitudes (Oksal, 2008) the intimacy of contact (Heinze and Horn, 2009;Smith et al, 2009) levels of aversion toward homosexuals (Ncanana and Ige, 2014); educational attainment, communicating with full-fledged activists, having an ability to recognize heterosexism and maintaining a commitment to social justice (Swank and Fahs, 2013) age, educational level, religious affiliation, contact with homosexual persons (Adela, 2010) higher levels of knowledge (Alderson et al, 2009) public policy (Hooghe and Meeusen, 2013) and government institution (Henshaw, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…There are several factors affecting those social supports. Swank and Fahs (2013) identified four factors: the level of education, communication, the ability to recognize heterosexuality and commitment to social justice. Meanwhile, Valenti and Campbell (2009) reported that the fear of losing jobs, stigma/social charge of -gay lifestyle‖ and the safety factor constitute obstacles for someone to provide support to gays.…”
Section: Introductionmentioning
confidence: 99%
“…While there is a wealth of research on predictors of attitudes towards war and militarism (e.g., Cohrs et al, 2005;Musgrove & McGarty, 2008), there is a limited amount of (particularly current) research on the specific issue of peace activism. Antecedents of involvement in peace activism have been identified in the literature, including high priority of the value of universalism (Mayton & Furnham, 1994), higher levels of education, activist identification and networks, specific foreign policy attitudes, and a positive view on the efficacy of protest (Swank & Fahs, 2011). Relevant qualitative work has investigated the mobilisation of identity in the talk of US peace activists (Hunt & Benford, 1994) or the ways in which Italian peace activists and non-activists represented war and peace (Sarrica & Contarello, 2004).…”
Section: Uk Peace Activismmentioning
confidence: 99%
“…Children, women, the elderly, people with disabilities, indigenous, and sexual minorities make up the majority of social work's target audience. Previous research examined the reasons why social work students engaged in LGBTQ human rights activism and concluded that the likelihood of students joining political protests was significantly affected by their desires to work for social justice (Swank & Fahs, 2013). Frontline social workers in Taiwan have participated in various social transformations such as child protection movement (Lin & Lee, 2016), the women's rights movement (Hsia, 2009), and the immigrant bride rights movement (Chang, 2009), which were good examples of the social/ political engagements that have raised the awareness for social work activism.…”
Section: Social Workers Are Protestersmentioning
confidence: 99%